Awareness of the Electronics Technology Students in Managing their E-waste: An Input for Developing an E-waste Management Policy - Goyal, John Kenneth C. (Future Science / FSH-PH Publications, 2023)
This study seeks to gauge the degree of awareness of the VALPOLY Electronics Technology students on E-waste management. A total of 188 VALPOLY EST students enrolled in the academic year 2022-2023 were purposively selected to participate in the research. An adapted and modified survey questionnaire was used to assess VALPOLY EST students' level of awareness and the challenges they faced in managing their e-waste. Frequency counts, percentages, means, the Mann-Whitney U test, and the Kruskal Wallis test were used for statistical analysis and data handling. All questions were rated on a 4-point Likert scale with a 0.5 level of significance. Based on the findings,